The Long Shadow of Port Infrastructure in Germany – Cause or Consequence of Regional Prosperity? - Philipp Breidenbach; Timo Mitze (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
Transport infrastructure is viewed as an important determinant of regional growth and development. While this prediction especially holds from a theoretical perspective based on endogenous growth theories, from an empirical perspective it is not easy to verify this causal link, though. The main reason for this difficulty is that it is hard to measure whether transport infrastructure is indeed the exogenous driver of regional development or whether it is rather an endogenous reflection of the higher transportation demand in prospering regions. In this paper, we analyse the long-run effect of port facilities on regional income levels in Germany. Since it is very likely that the 'reversed causality' problem applies to our sample setting, we use an identification strategy that is based on exogenous longrun instruments. In particular, port facilities built before the industrial revolution (about 1850 in Germany) can be seen as an adequate instrument for current port infrastructure since they are exogenous to recent economic development. Using German regional data for 1991-2008, our results hint at a positive correlation between port locations and regional per capita GDP, but do not provide evidence for a causal relationship. For the regional variation of population levels as a more general indicator for agglomeration effects, the causal relationship running from port infrastructure provision to increasing population levels holds nonetheless.
Keywords: C26; R12; R40; 330; port infrastructure; regional income; causal effects; IV